A Methodology for Characterizing Real-Time Multimedia Quality of Service in Limited Bandwidth Network - Yoanes Bandung; Idi Sumardi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper presents how to characterize the quality of multimedia which consists of audio and video that are transmitted in real-time communication through the Internet with limited bandwidth. We developed a methodology of characterizing the multimedia Quality-of-Service (QoS) by measuring network parameters (i.e., bandwidth capacity, packet loss rate (PLR), and end-to-end delay) of testbed network and simulating the audio-video delivery according to the measured network parameters. The analysis of network parameters was aimed to describe the network characteristics. Multimedia QoS was characterized by conducting a simulation using data which was collected from the previous network characterization. A simulation network model was built using OMNet++ representing a delivery of audio-video in real-time while a background traffic was generated to represent a real condition of the network. Apllying the methodology in a network testbed in Indonesia’s rural area, the simulation results showed that audio-video could be delivered with accepted level of user satisfaction.